Clinical features and differential diagnosis of type 2 diabetes mellitus in children - Tamara Leonidovna Kuraeva; I A Dubinina (Сахарный диабет)
This review was designed to evaluate prevalence, specific clinical features, and differential diagnosis of type 2 diabetes mellitus (DM2) in childrenand adolescents. Special emphasis is laid on the importance of immunological and molecular-genetic studies for the verification of diagnosis and activecase detection in h groups.